Association between Blood Pressure and HIV Status in Rural Uganda: Results of Cross-Sectional Analysis. Issue 1 (10th February 2021) - Niwaha, Anxious J.; Wosu, Adaeze C.; Kayongo, Alex; Batte, Charles; Siddharthan, Trishul; Kalyesubula, Robert; Kirenga, Bruce; Checkley, William
Introduction: The association between HIV status and hypertension is not well described within sub-Saharan Africa. We examined prevalence and risk factors for hypertension among HIV positive and negative individuals living in a rural district of Uganda. Methods: We conducted a cross-sectional analysis in two concurrent cohorts of 600 HIV negative and 721 HIV seropositive individuals aged ≥35 years. Results: Of the 721 HIV positive participants, 59.8% were women and the median age was 44.3 years, while for HIV negative individuals, 55% were women and the median age was 47.8 years. Over 90% of HIV positive individuals were on antiretroviral treatment. The prevalence of hypertension (≥140/≥90 mmHg) was 33.5% in HIV negative individuals and 23.9% in HIV positive individuals. Age (adjusted OR = 1.05, 95% CI 1.03 to 1.06) and BMI (adjusted OR = 1.08, 95% CI 1.05 to 1.12) were associated with higher odds of hypertension. Having HIV was associated with lower odds of hypertension (adjusted OR = 0.66, 95% CI 0.50 to 0.88), lower systolic blood pressure (–5.1 mmHg, 95% CI: –7.4 to –2.4) and lower diastolic blood pressure (–4.0 mmHg, 95% CI: –5.6 to –2.5). We did not observe differences in the odds of hypertension by CD4 count, viral load or ART among HIV positive individuals in this sample. Conclusions: Hypertension was prevalent in one third of HIV negative individuals and in one fourth of HIV positive patients. While access to health information among individuals attending HIV clinics may explain observed differences, more research is needed to understand plausible biological and social mechanisms that could explain lower blood pressure among people living with HIV in Uganda.